„Wojny o naukę" – geneza, strony konfliktu i problemy do rozwiązania - Kazibut, Radosław (My University, 2013)
Science Wars – Origin, Warring Parties and the Problems To Be Solved ABSTRACT. This article presents the genesis and the sides of the discussion which is held as part of the so-called “science wars”. Certain methodological aspects of “science war” after the “Sokal haox” are discussed here. The term “science wars” refers to a popular debate that is taking place not only across the academic disciplines but also in the popular media. “Science wars” are waged between scientists who believe that science and its methods are objective and an increasing number of social scientists, historians, philosophers, and others gathered under the umbrella of “science studies”.
Keywords: science wars; Sokal’a hoax; two cultures; SSK; methodological relativism; antiscience